Excess Pressure Integral Predicts Long-Term All-Cause Mortality in Stable Heart Failure Patients. (12th November 2016) - Wang, Wei-Ting; Sung, Shih-Hsien; Wang, Jiun-Jr; Wu, Cho-Kai; Lin, Lian-Yu; Lee, Jia-Chun; Cheng, Hao-Min; Chen, Chen-Huan
Abstract: BACKGROUND: Excess pressure integral (XSPI) derived from reservoir-excess pressure analysis is proposed as a novel indicator of cardiovascular dysfunction in hypertensives. Our study investigated the prognostic value of XSPI for stable heart failure (HF) patients. METHODS: In total, 238 subjects (mean age 63 ± 18 years, 111 male), comprising 168 stable HF patients with either reduced (SHF; n = 64) left ventricular (LV) ejection fraction (EF) or isolated diastolic dysfunction (DHF, n = 104), and 70 healthy controls, were enrolled. Tonometry-derived carotid pressure waveforms were analyzed with the reservoir pressure theory. XSPI was calculated by subtracting the reservoir pressure from carotid pressure waveform. RESULTS: XSPI in SHF and DHF (14.01 ± 5.16 and 13.90 ± 5.05 mm Hgs) were significantly higher than that in controls (11.01 ± 3.67 mm Hgs, both P < 0.001). During a median follow-up of 9.9 years, 56 deaths occurred. XSPI was a significant independent predictor of total mortality after adjusting for age, sex, left ventricular ejection fraction (LVEF), glomerular filtration rate (GFR), and N-terminal pro-B-type natriuretic peptide (NT-proBNP) (hazard ratio = 4.37 per 1 SD, 95% confidence interval, 1.31–14.58). In subgroup analysis by different baseline characteristics including age, gender, NT-proBNP, LVEF, and GFR, higher XSPI was consistently associated with greater risk of total mortality. CONCLUSION: In patients with stable HF, XSPI, a novel maker of cardiovascular dysfunction, was associated with long-term risk of total mortality.